2014
DOI: 10.1117/12.2045683
|View full text |Cite
|
Sign up to set email alerts
|

High contrast optical imaging methods for image guided laser ablation of dental caries lesions

Abstract: Laser based methods are well suited for automation and can be used to selectively remove dental caries to minimize the loss of healthy tissues and render the underlying enamel more resistant to acid dissolution. The purpose of this study was to determine which imaging methods are best suited for image-guided ablation of natural non-cavitated carious lesions on occlusal surfaces. Multiple caries imaging methods were compared including near-IR and visible reflectance and quantitative light fluorescence (QLF). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
4

Relationship

8
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…[18] Surface roughening can scatter light which may increase the reflectivity and confound image guided ablation, moreover it also can be aesthetically displeasing. [18] Therefore, it is important to choose laser scanning parameters that minimize surface roughening. The influence of varying the fluence and the spatial overlap of the laser pulses was also investigated.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Surface roughening can scatter light which may increase the reflectivity and confound image guided ablation, moreover it also can be aesthetically displeasing. [18] Therefore, it is important to choose laser scanning parameters that minimize surface roughening. The influence of varying the fluence and the spatial overlap of the laser pulses was also investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, an image-guided computer-controlled laser is ideal for selectively removing caries lesions. Previous work demonstrated that the CO 2 laser irradiated enamel does not interfere with the ability to image the tooth surface nor significantly distort the contrast between sound and carious dental hard tissues [7]. Furthermore, in past near-IR image-guided laser experiments, InGaAs cameras were successful in detecting lesion presence and guiding a CO 2 laser for lesion removal [8].…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 lasers (λ = 9.3–9.6-µm) have been shown to be well suited for caries removal and CO 2 laser pulses can be used to render dental enamel to be more resistant to further decay [7]. Previous work was done to show that the laser irradiated enamel does not interfere with the ability to image the tooth surface at near-IR wavelengths nor significantly distort the contrast between sound and demineralized dental hard tissues [8]. Typical dental lasers are operated by hand, which nullifies their capacity for high precision and selectivity.…”
Section: Introductionmentioning
confidence: 99%